Ring opening of cyclic thioimidates in reaction with active methylene compounds. Issue 40 (7th October 2015) - Shvydenko, Kostiantyn; Nazarenko, Kostiantyn; Shvydenko, Tetiana; Vlasenko, Yurii; Tolmachev, Andrei; Kostyuk, Aleksandr
Abstract: The reaction of cyclic thioimidates with active methylene compounds in the presence of acetic acid anhydride was studied. In case of six- and seven-membered derivatives the reaction proceeded via substitution of thiomethoxy group affording cyclic enamines. In case of five-membered derivatives the reaction proceeded via opening of the thioimidate ring affording functionalized aminopropane derivatives. Graphical abstract: